Pedigree‐based analysis of derivation of genome segments of an elite rice reveals key regions during its breeding. Issue 2 (10th June 2015) - Zhou, Degui; Chen, Wei; Lin, Zechuan; Chen, Haodong; Wang, Chongrong; Li, Hong; Yu, Renbo; Zhang, Fengyun; Zhen, Gang; Yi, Junliang; Li, Kanghuo; Liu, Yaoguang; et al.
Summary: Analyses of genome variations with high‐throughput assays have improved our understanding of genetic basis of crop domestication and identified the selected genome regions, but little is known about that of modern breeding, which has limited the usefulness of massive elite cultivars in further breeding. Here we deploy pedigree‐based analysis of an elite rice, Huanghuazhan, to exploit key genome regions during its breeding. The cultivars in the pedigree were resequenced with 7.6× depth on average, and 2.1 million high‐quality single nucleotide polymorphisms (SNPs) were obtained. Tracing the derivation of genome blocks with pedigree and information on SNPs revealed the chromosomal recombination during breeding, which showed that 26.22% of Huanghuazhan genome are strictly conserved key regions. These major effect regions were further supported by a QTL mapping of 260 recombinant inbred lines derived from the cross of Huanghuazhan and a very dissimilar cultivar, Shuanggui 36, and by the genome profile of eight cultivars and 36 elite lines derived from Huanghuazhan. Hitting these regions with the cloned genes revealed they include numbers of key genes, which were then applied to demonstrate how Huanghuazhan were bred after 30 years of effort and to dissect the deficiency of artificial selection. We concluded the regions are helpful to the further breeding based on this pedigree and performing breeding by design. Our study provides genetic dissection of modern rice breeding and sheds new light on how to perform genomewide breeding by design.